The Principal Ocean Trade Routes of the World (Harper & Brothers, 1885)
This map shows the world with major trade routes marked. The routes are shown in red lines and black dotted lines with labels and some notes regarding transit times. Major cities and exports are labeled; bodies of water and geographic features are also marked (with relief shown in hachures). There is text beneath the map labeled "Questions on the Map." Prime meridians: Greenwich and Washington. On the back of the map there are two pages of text. On the left, the text is titled "Physical Geography -- General Review" and includes general questions about geography. The text on the right page is labeled "Abyssinia. -- Negro Africa: South Central Africa and African Islands" and includes general information about the geography and commerce of Africa.